Laminin β2 Chain Regulates Cell Cycle Dynamics in the Developing Retina - Serjanov, Dmitri; Bachay, Galina; Hunter, Dale D.; Brunken, William J. (Frontiers in Cell and Developmental Biology, 2022)
Vertebrate retinal development follows a highly stereotyped pattern, in which the retinal progenitor cells (RPCs) give rise to all retinal types in a conserved temporal sequence. Ensuring the proper control over RPC cell cycle exit and re-entry is, therefore, crucially important for the generation of properly functioning retina. In this study, we demonstrate that laminins, indispensible ECM components, at the retinal surface, regulate the mechanisms determining whether RPCs generate proliferative or post-mitotic progeny. In vivo deletion of laminin β2 in mice resulted in disturbing the RPC cell cycle dynamics, and premature cell cycle exit. Specifically, the RPC S-phase is shortened, with increased numbers of cells present in its late stages. This is followed by an accelerated G2-phase, leading to faster M-phase entry. Finally, the M-phase is extended, with RPCs dwelling longer in prophase. Addition of exogenous β2-containing laminins to laminin β2-deficient retinal explants restored the appropriate RPC cell cycle dynamics, as well as S and M-phase progression, leading to proper cell cycle re-entry. Moreover, we show that disruption of dystroglycan, a laminin receptor, phenocopies the laminin β2 deletion cell cycle phenotype. Together, our findings suggest that dystroglycan-mediated ECM signaling plays a critical role in regulating the RPC cell cycle dynamics, and the ensuing cell fate decisions.